Consumer Inference: A Review of Processes, Bases, and Judgment Contexts - Kardes, Frank R.; Posavac, Steven S.; Cronley, Maria L. (Journal of Consumer Psychology, 2004)
Because products are rarely described completely, consumers often form inferences that go beyond the information given. We review research on the processes, bases, and the judgment contexts in which inferences are formed. The most basic processes are induction (inferences from specific instances to general principles) versus deduction (inferences from general principles to specific instances). Stimulus‐based inferences are formed on‐line (as information is encountered) using situationally available information, whereas memory‐based (or theory‐based) inferences are formed using prior knowledge and experience. Inferences can pertain to a single product judged in isolation (a singular judgment context) or to multiple products considered in relation to one another (a comparative judgment context). This 2x2x2 (Induction vs. Deduction x Stimulus‐Based vs. Memory‐Based x Singular vs. Comparative Judgment) theoretical framework suggests that there are 8 different types of inferences that consumers may form. Based on this framework, we identify gaps in the literature and suggest directions for future research.